Keberhasilan Usaha Kuliner Dilihat Dari Faktor Karakteristik dan Pengetahuan Kewirausahaan (Studi Kasus Usaha Kuliner Ayam Penyet) - Nasution, Amrin Mulia Utama; Lailikhatmisafitri, Isnaniah; Marbun, Patar (Mahesa Research Center, 2021)
This study aims to determine the success of the culinary business. Judging from the Characteristics and Knowledge of Entrepreneurship in the Penyet Chicken culinary business, the research was conducted in several locations of the Ayam Penyet culinary business in Medan Tembung and Medan Perjuangan districts. When the research was conducted from August 2020 to September 2020 the number of samples in this study were 35 respondents with Characteristics Variables (X1), which had a positive and significant effect on business success, this was seen from the significant value (0.034) <0.05 and the t value (2.225 )> t table (1,988), meaning that even though the knowledge variable is increased by one unit (unit), the success of the Penyet Chicken Culinary business (Y) will increase by 0.424 units (units). Knowledge variable (X2) has a positive and significant effect on business success, this can be seen from the significant value (0.041) <0.05 and the t value (2.132)> t table (1.988) means that if the characteristic variable is increased by one unit (unit) then the success of the Penyet Chicken Culinary business (Y) will increase by 0.530 units (units). The results of the F test show that the Entrepreneurial Characteristics and Entrepreneurial Knowledge simultaneously have a significant effect on the Success of Penyet Chicken Culinary Business.